2016
DOI: 10.1016/j.applanim.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine via drinking water and combined oral-injection protocols for pain relief in mice

Abstract: Buprenorphine is the opioid most commonly used in laboratory mice. To maintain therapeutic serum levels, repeated injections are required. Oral self-administration is an alternative but has been criticized to be unreliable. Here we analyse voluntary intake and water/injection combinations for their reliability to achieve effective drug supply. Mice were assigned to one of five groups: a) naïve (N); b) buprenorphine via water for 24 h (W); c) buprenorphine via two injections during light, and via water during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
1
22
2
Order By: Relevance
“…Furthermore, the uptake of paracetamol with the drinking water might be decreased after anaesthesia and surgery, but data obtained in this study and from other publications (Cesarovic et al, 2010;Sauer et al, 2016) show, that no relevant alteration of drinking behaviour occurred after inhalation anaesthesia with or without surgery. However, in case of doubts regarding uptake of the drug in the immediate post-anaesthetic phase, one may administer the analgesic then as a single bolusinjection to compensate for a suspected delay in drinking after the intervention.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, the uptake of paracetamol with the drinking water might be decreased after anaesthesia and surgery, but data obtained in this study and from other publications (Cesarovic et al, 2010;Sauer et al, 2016) show, that no relevant alteration of drinking behaviour occurred after inhalation anaesthesia with or without surgery. However, in case of doubts regarding uptake of the drug in the immediate post-anaesthetic phase, one may administer the analgesic then as a single bolusinjection to compensate for a suspected delay in drinking after the intervention.…”
Section: Discussioncontrasting
confidence: 65%
“…Low water intake during the pre-operative phase could have been due to the still unfamiliar taste of the water, and to generally lower water intake at the beginning of the light period. Water consumption during the day time tends to be less and more sporadic than during night time due to circadian rhythmicity (Sauer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 116 However, medication of food or water has more variable effects, and it is important to ensure that the analgesic is reliably consumed, in sufficient quantity. 117 For example, intake of analgesics in water may be unreliable for animals that are less mobile, or where the taste of the water is altered by adding the drug. Administration in food and water may be ineffective, since food and water consumption are greatly influenced by diurnal rhythms, and animals may receive ineffective doses during the light phase of their photoperiod.…”
Section: Anaesthesia and Analgesiamentioning
confidence: 99%
“…Moreover, latency to ingestion as well as the total amount ingested by the animals, especially during the resting phase, is difficult to anticipate and is clearly variable for each individual. Thus, voluntary ingestion protocols might be applicable only when pain is mild, or in combination with drug injections, at least during the resting phase of rodents 24 .…”
Section: Effect Of Analgesia Protocolsmentioning
confidence: 99%
“…Voluntary oral administration of analgesia is another promising approach that avoids the negative effects of handling. Several routes of oral administration have been described, such as mixing analgesics with flavored gelatine 21 , Nutella 22 , regular diet 23 or drinking water 24 . These studies in mice and rats have shown that several analgesics are efficient when administered orally and voluntarily.…”
Section: Effect Of Analgesia Protocolsmentioning
confidence: 99%